Penerapan Flashcard Berbasis Karakter Flora dan Fauna Untuk Meningkatkan Kemampuan Mengenal Huruf Peserta Didik Tunagrahita Sedang SLB Siswa Budhi - Qurrota A’yuni; Mirna Veanda Rista Agustin; Dian Nur Cahyani; Muhammad Dian Nazarudin; Mega Nur Karisma (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to describe the learning outcomes of students who are taught using flashcard learning media for students of SLB Siswa Budhi and to find out whether there are differences in learning outcomes for students who are taught before and after being taught using flashcard learning media based on flora and fauna. The ability to read and recognize children's letters is influenced by the learning media used. This can be seen from the application of flashcard learning media. Data was collected from three students of SLB Siswa Budhi. This research is a descriptive qualitative research. At the data collection stage, the researcher used the listening method and experimental research, the listening method was listening to the children's speech which they obtained before and after the application of flashcard learning media. Therefore this research concerns the application of flora and fauna character-based flashcards to improve the ability to recognize letters of moderately mentally retarded students. This research resulted that the application of flashcard learning media is good and appropriate to be used as a learning medium because it can improve the ability to read and recognize letters of students with moderate mental retardation.